Unveiling the Antioxidant Power and Secondary Metabolites of Tabebuia chrysantha (Jacq.) Leaves and Flowers from Ecuador - Raluca A. Mihai; Ramiro Fernando Vivanco Gonzaga; Nelson Santiago Cubi Insuaste; Nilo Rigoberto Maza Morocho; Rodica D. Catana (Pharmaceuticals)
Background: Tabebuia chrysantha (Jacq.) Nichols, commonly known as Guayacan, is a prominent species within the Bignoniaceae family known for its medicinal value and ecological significance. This study aimed to characterize the antioxidant capacity and secondary metabolite composition of Guayacan leaves and flowers grown in Ecuador, a region where its chemical profile remains unexplored. Methods: Comprehensive analyses were conducted to determine the total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity using ABTS, DPPH, FRAP assays, and LC-MS. Results: The results revealed remarkable differences between mature leaves and flowers. Leaves exhibited consistently higher flavonoid levels (e.g., 0.280 ± 0.005 mg QE/g DW) and superior antioxidant capacity across all assays (e.g., 10.84 ± 0.51 µmol Trolox g−1 DW in ABTS) compared to flowers, which showed greater variability but lower overall activity. These findings highlight a functional specialization, with leaves synthesizing more flavonoids to mitigate oxidative stress from environmental factors such as UV radiation. LC-MS analysis unveiled various bioactive compounds, including phenolic acids, flavonoids, and terpenoids. Unique metabolites like α-lipoamide in leaves and oleanolic acid in flowers suggest distinct adaptive roles, potentially linked to stress tolerance and reproductive functions. Additionally, strong correlations among antioxidant assays (e.g., FRAP vs. DPPH, r = 0.993, p < 0.001) emphasize the pivotal role of phenolics and flavonoids in free radical scavenging and reduction mechanisms. Conclusions: The findings of this study demonstrate the superior antioxidant capacity of leaves, driven by their higher accumulation of flavonoids and phenolic compounds. This research represents a foundational step toward uncovering the therapeutic potential of Ecuadorian Guayacan as a source of natural antioxidants and bioactive compounds, supporting its future applications in phytotherapy and drug development.